Evidence for a PGF2α auto-amplification system in the endometrium in mares. Issue 5 (May 2016) - Kozai, Keisuke; Tokuyama, Shota; Szóstek, Anna Z; Toishi, Yuko; Tsunoda, Nobuo; Taya, Kazuyoshi; Sakatani, Miki; Takahashi, Masashi; Nambo, Yasuo; Skarzynski, Dariusz J; Yamamoto, Yuki; Kimura, Koji; et al.
Abstract: In mares, prostaglandin F2α (PGF2α ) secreted from the endometrium is a major luteolysin. Some domestic animals have an auto-amplification system in which PGF2α can stimulate its own production. Here, we investigated whether this is also the case in mares. In an in vivo study, mares at the mid-luteal phase (days 6–8 of estrous cycle) were injected i.m. with cloprostenol (250 µg) and blood samples were collected at fixed intervals until 72 h after treatment. Progesterone (P4 ) concentrations started decreasing 45 min after the injection and continued to decrease up to 24 h (P < 0.05). In turn, 13, 14-dihydro-15-keto-PGF2α (PGFM) metabolite started to increase 4h after an injection and continued to increase up to 72 h (P < 0.05). PGF receptor ( PTGFR ) mRNA expression in the endometrium was significantly higher in the late luteal phase than in the early and regressed luteal phases (P < 0.05). In vitro, PGF2α significantly stimulated (P < 0.05) PGF2α production by endometrial tissues and endometrial epithelial and stromal cells and significantly increased (P < 0.05) the mRNA expression of prostaglandin-endoperoxide synthase-2 ( PTGS2 ), an enzyme involved in PGF2α synthesis in endometrial cell. These findings strongly suggest the existence of an endometrial PGF2α auto-amplification system in mares.